Implementation of “Kampus Mengajar" Programs to Improve Learning Motivation - Suprima Suprima; Akmal Rizki Gunawan Hasibuan; Fadhilah Qurratu 'Ayuni (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This dedication is carried out to implement various activities of the 3rd Kampus Mengajar Program to motivate students to learn at Middle School 2 Pamarican. After observing the school, multiple problems were found, such as students' lack of enthusiasm during learning due to their lack of extrinsic motivation, students still needing help to read and count correctly, and teachers still using traditional learning media. This study used a qualitative descriptive method with data collection techniques through teacher interviews and school observations. This research was conducted at Middle School 2 Pamarican for four months, from March 2nd, 2022, to June 29th, 2022. This research was aimed at students in grades VII and VIII and was carried out directly. The results of this dedication activity include assisting in teaching, learning multiplication using jarimatika, operating numbers, arithmetic series, and the concept of 3 M with the GASING method, improving reading skills using five methods, learning to recite the Quran, and adapting technology aimed at increasing students' learning motivation. There were many obstacles and challenges during the implementation, especially when learning became limited, so teachers had to have high creativity to improve student learning outcomes.